2019
DOI: 10.36380/scil.2019.wvj26
|View full text |Cite
|
Sign up to set email alerts
|

Productive Characteristics and Reproductive Responses to Estrus Synchronization and Flushing in Abou-Delik Ewes Grazing in Arid Rangelands in Halaieb - Shalateen - Abouramad Triangle of Egypt.

Abstract: There are a few reports about the reproductive aspects or uses of both of flushing and estrus synchronization in Abou-Delik ewes grazing in the South Eastern zone of Egypt. Thirty-three Abou-Delik ewes were allocated to three experimental groups (n = 11 in each) to study the effects of estrus synchronization and flushing on reproductive responses and productive characteristics under arid conditions of South Eastern zone of Egypt. Group one served as control represent the system dominant in the area (without es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
0
1
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 25 publications
(31 reference statements)
4
0
1
10
Order By: Relevance
“…Feeding ewes at a level below maintenance results in loss of live weight (LW) and body condition score (BCS) and, during mating, severely reduces lambing percentage (McWilliam et al, 2005). The present results of prolificacy agreed with those reported by Farrag (2019), where prolificacy in Abou-Delik sheep increased as a consequence of increasing feed provided to ewes. Grazing sheep in the Halaieb triangle, like other Egyptian sheep, are characterized by pretty good fertility rates, an extended breeding season, but low prolificacy (Gabr et al, 2016), thus not significantly influenced by seasonality (i.e., ewes cycle all year round), which occurs due to slight variations in day length throughout the year.…”
Section: Discussionsupporting
confidence: 88%
“…Feeding ewes at a level below maintenance results in loss of live weight (LW) and body condition score (BCS) and, during mating, severely reduces lambing percentage (McWilliam et al, 2005). The present results of prolificacy agreed with those reported by Farrag (2019), where prolificacy in Abou-Delik sheep increased as a consequence of increasing feed provided to ewes. Grazing sheep in the Halaieb triangle, like other Egyptian sheep, are characterized by pretty good fertility rates, an extended breeding season, but low prolificacy (Gabr et al, 2016), thus not significantly influenced by seasonality (i.e., ewes cycle all year round), which occurs due to slight variations in day length throughout the year.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, Zarkawi (2000) reported that the treatment had no effect on the duration of pregnancy, which averaged 150.3 days in control and 150.4 and 150.8 days in synchronized groups with 10 and 15 mg PGF2α, respectively. Whereas, pregnancy period in the present study was lower than that reported by Farrag (2019) who found that the average gestation length period were 157.37 and 154.88 days for control ewes and PGF 2α ewes, respectively in Abou-Delik ewes grazing in the South Eastern zone of Egypt. Also, Safranski et al (1992) who found that pregnancy periods in control ewes and ewes treated with melengesterol acetate (MGA) + PG-600 were 163.8 and 157.2 days, respectively in Kalkuhi ewes in Iran.…”
Section: Discussioncontrasting
confidence: 87%
“…Results found between Bapedi sheep and Zulu sheep were similar to that reported previously by Kridli et al (2009); Zeleke et al (2005) and Mansur et al (2018) where lambing rate could not differ among breeds and their lactation statuses. The conception and lambing rate of Zulu sheep and Bapedi sheep were comparable to Farrag (2019) results who reported that, oestrus synchronization result in higher conception rate on the Abou-Delik sheep.…”
Section: Discussionsupporting
confidence: 85%